A novel NiCo2S4-based capacitive material with a homogeneous and heteromorphic construction. (1st November 2022) - Fu, You; Liu, Xilong; Han, Leiyun; Xie, Zheng; Chen, Huaxia; Hua, Yingjie; Wang, Chongtai
Abstract: Aim to improve the capacitive performance of the NiCo2 S4 -based electrode materials, a novel composite material with a homogeneous and heteromorphic construction, h -NiCo2 S4 / u -NiCo2 S4 /NF, was successfully prepared through layer-by-layer growth in a hydrothermal process using urea and hexamethylenetetramine as alkali source in this work. This material presents a specific capacity high up to 1245.3 C g −1 (345.9 mAh g −1 ) at the current density of 2 A g −1 in a 6 M KOH electrolyte solution. Moreover, a 74.6 % of the initial specific capacity is still retained when the current density increases from 2 to 10 A g −1, showing a relatively good rate capability. Especially, an 84.0 % of capacity retention rate can be obtained after it suffers from 7000 charging-discharging cycles at 50 mA cm −2 (9.2 A g −1 ), exhibiting a good cycling stability. Using it as the positive electrode material to assemble an asymmetrical supercapacitive device with a home-made porous carbon (PC) as the negative electrode material, an energy density high up to 48.4 Wh kg −1 at 1060.6 W kg −1 and a 63.2 % of capacity retention rate at 10, 000 charging-discharging cycles can be achieved, superior to many NiCo2 S4 -based asymmetrical supercapacitive devices reported so far. Graphical abstract: Unlabelled Image Highlights: A novel NiCo2 S4 -based electrode material h -NiCo2 S4 / u -NiCo2 S4 /NF for supercapacitors was successfully prepared. The prepared electrode material can provide a specific capacity high up to 1245.3 C g -1 at 2 A g -1 . The prepared electrode material possesses a superior rate capability and charge-discharge cycling stability. An asymmetric supercapacitor device assembled using this material can deliver an energy density of 48.4 Wh kg -1 at 1060.6 W kg -1 .